2011
DOI: 10.1038/ngeo1050
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen isotope ratios in lunar rocks indicate delivery of cometary water to the Moon

Abstract: Hydrogen isotope ratios in lunar rocks and the delivery of cometary water to the MoonWater plays a critical role in the evolution of planetary bodies 1 , and determination of the amount and sources of lunar water has profound implications for our understanding of the history of the Earth-Moon system. During the Apollo program, the lunar samples were found to be devoid of indigeneous water 2,3 . The severe depletion of lunar volatiles 4 , including water, has long been seen as strong support for the giant-impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
238
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(257 citation statements)
references
References 23 publications
(18 reference statements)
17
238
2
Order By: Relevance
“…Our detection of SW-produced water in rims on silicate mineral grains in nominally anhydrous IDPs has implications for production of water on the surfaces of airless bodies, its delivery to the surface of the Earth and other terrestrial planets, and production of water in the interstellar medium (3)(4)(5)13). † For example, there is intense interest in water at the poles of the Moon (10,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our detection of SW-produced water in rims on silicate mineral grains in nominally anhydrous IDPs has implications for production of water on the surfaces of airless bodies, its delivery to the surface of the Earth and other terrestrial planets, and production of water in the interstellar medium (3)(4)(5)13). † For example, there is intense interest in water at the poles of the Moon (10,(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…† For example, there is intense interest in water at the poles of the Moon (10,(25)(26)(27). A fundamental and as-yet unresolved question is the source of the water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, direct measurements of water in incompletely degassed, primitive lunar glasses made in several laboratories have shown that water concentrations are similar to those observed in magmas from Earth's depleted upper mantle (Saal et al 2008;Chen et al 2015;Hauri et al 2015;Wetzel et al 2015) and that the isotopic composition of this water is approximately chondritic (Friedman et al 1974;Saal et al 2013;Barnes et al 2014;Füri et al 2014;Tartèse et al 2014). Although these results and their generality to the Moon as a whole are not universally accepted (Sharp et al 2010;Greenwood et al 2011;Albarède et al 2015), these observations have been interpreted as signifying a common origin for terrestrial and lunar water ). The incorporation of water into the Moon in concentrations similar to those of the Earth is seemingly at odds with the widely held view of the origin of the Moon as the result of an impact between the early Earth and a Mars-sized impactor (e.g., Canup and Asphaug 2001;Pahlevan and Stevenson 2007).…”
Section: Introductionmentioning
confidence: 94%
“…Recent detections of dissolved water in lunar volcanic glasses and melt inclusions (Saal et al 2008;Hauri et al 2011;Saal et al 2013;Chen et al 2015;Wetzel et al 2015), lunar apatites (Boyce et al 2010;McCubbin et al 2010;Greenwood et al 2011;Tartèse et al 2014), and plagioclase from lunar highland anorthosites (Hui et al 2013) have led to a reevaluation of what has appeared for decades to be one of the definitive results of the study of lunar samples: i.e., that the sources of lunar magmas-and, by inference, the entire Moon-are much poorer in water than the Earth; indeed the Moon had been described as "bone dry" (Newsom and Taylor 1989). In particular, direct measurements of water in incompletely degassed, primitive lunar glasses made in several laboratories have shown that water concentrations are similar to those observed in magmas from Earth's depleted upper mantle (Saal et al 2008;Chen et al 2015;Hauri et al 2015;Wetzel et al 2015) and that the isotopic composition of this water is approximately chondritic (Friedman et al 1974;Saal et al 2013;Barnes et al 2014;Füri et al 2014;Tartèse et al 2014).…”
Section: Introductionmentioning
confidence: 99%